2018
DOI: 10.5539/jps.v7n1p19
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Medicinal Uses and Pharmacological Activities of Tridax Procumbens (L.)

Abstract: Tridax procumbens is a very promising species that produces secondary metabolites reported to have a variety of medicinal uses including among others, anti-anemic, anti-inflammatory, anti-diabetic and anesthetic properties. This species has a long history of traditional use by different communities. This study aimed to review the scientific literature regarding the medicinal properties, biological activity and phytochemical components of T. procumbens, a member of the Asteraceae family that originated in Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 54 publications
(74 reference statements)
0
20
0
Order By: Relevance
“…Tridax procumbens is a very promising species that produces secondary metabolites reported to have a variety of medicinal uses including among others, anti-anemic, anti-inflammatory, anti-diabetic and anesthetic properties [41]. Essential oils extracted from T. procumbens are reported to have insecticidal activity against Musca domestica, Culex quinquefasciatus, Dysdercus similis and Supella spp.…”
Section: Tridax Procumbens L (Asteraceae)mentioning
confidence: 99%
“…Tridax procumbens is a very promising species that produces secondary metabolites reported to have a variety of medicinal uses including among others, anti-anemic, anti-inflammatory, anti-diabetic and anesthetic properties [41]. Essential oils extracted from T. procumbens are reported to have insecticidal activity against Musca domestica, Culex quinquefasciatus, Dysdercus similis and Supella spp.…”
Section: Tridax Procumbens L (Asteraceae)mentioning
confidence: 99%
“…Several studies have reported the smooth muscle/vaso-relaxant and antihypertensive potential of Tridax procumbens leaf extract (TPE) [ 3 - 5 ]. T. procumbens has been used to produce emollients, beverages, and skincare products, and the extensive use of the plant is associated with its protective properties and phytochemical constituents [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of fatalities because of respiratory disorders and associated complications have been reported [ 7 , 8 ]. The most commonly used drugs for asthmatic conditions are fast-acting β2-agonists [ 9 ] and anticholinergics [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is mostly occurs in desert and cold or semi-desert climates. Following workers work on the members of Family Asteraceae Baker 1970;Trease and Evan 1983;Murray et al 1989;Gibson et al 1998;Tabuti et al Dillard and German 2000;2003;Farinola and Piller 2005;Karunkar and Joshi 2010;Mundada and Shivhare 2010;Pai 2011;Sawant and Godghate 2013;Ahmad et al, 2018;Beck et al, 2018;Bharathi andUdaya kumar 2019 andAhmad et al, 2020.…”
Section: Introductionmentioning
confidence: 99%